The effectiveness of natural tooth whitening using herbal substances on coffee-induced tooth discoloration - Purba, Member Reni; Tarigan, Gabriel C.J.; Lokanata, Shieny (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Tooth discoloration can be caused by many factors, including food and beverages. One of the drinks that can affect tooth color is coffee. Tooth discoloration can be overcome by teeth whitening procedures, which often use chemicals that can cause tooth sensitivity. Therefore, in this study, researchers are looking for safer alternatives, namely using herbal ingredients such as kepok banana peel and pineapple stem. This study used a laboratory experimental method with a pre-test and post-test only research design with control groups. The sample consisted of 27 central and lateral incisor teeth, which were divided into three treatment groups. The samples were then soaked for 14 days in coffee solution, and then group one was soaked in 100% kepok banana peel extract, group two was soaked in 100% pineapple stem extract, and group three as a control group was soaked in 6% hydrogen peroxide. All samples were soaked for two days in an incubator. The results of the one-way ANOVA test showed that there was a significant color difference (p<0.05) between the three treatment groups. The Post Hoc LSD test showed there was a significant difference between the 6% hydrogen peroxide group and the two extract groups, and also a significant difference between 100% kepok banana peel and 100% pineapple stem extract. Each group has an effect on tooth discoloration. Hydrogen peroxide is indeed the group with the highest tooth color change but has an effect that can make teeth sensitive. The banana peel and pineapple stem extract groups also had a significant and safer effect on teeth. 100% kepok banana peel extract and 100% pineapple stem extract have an effect on tooth discoloration but are not better than hydrogen peroxide. In addition, 100% pineapple stem extract has a better ability in teeth whitening than 100% kepok banana peel extract.